Megabenthic assemblages on bathyal escarpments off the west Corsican margin (Western Mediterranean). (May 2021) - Grinyó, Jordi; Chevaldonné, Pierre; Schohn, Thomas; Le Bris, Nadine
Abstract: Deep-sea environments in the Mediterranean Sea have been widely degraded over the past decades and thus there is an urgent need to implement protection measures. Within European Union's Mediterranean waters vast extensions of the deep-sea ecologically relevant ecosystems have been protected by integrating them to the Natura 2000 network. Inside the French Exclusive Economic Zone, this network is currently expanding to off-shore areas, beyond 12 nautical miles. In this study, we characterized megabenthic biodiversity on target features located inside a designed site of the south west Corsican margin, particularly on a volcanic promontory on the south flank of the Ajaccio submarine canyon and a wall of the Valinco Canyon, between 1690 and 2250 m depth. By means of a fine scale three-dimensional photogrammetric analysis, four megabenthic assemblages segregated by substrate were identified. Hard substrate assemblages were characterized by the presence of sponges, polychaetes, gastropods and the squat lobster Munida tenuimana while soft sediment assemblages were characterized by the elpidiid holothurian Penilpidia ludwigi and an unidentified sabellid. Highest densities were registered on serpulid thanatocoenoses, which hosted widespread patches of an unidentified encrusting sponge. Lebensspuren had a diverse origin likely deriving from the activity of epibenthic, infaunal and bathypelagic organisms. In general, litter was not abundant at these offshore sites: in the Valinco site, it had both a marine and land-based origin while at the even more offshore Ajaccio site, it was mainly marine based. More extensive surveys would be advisable to confirm this trend. This study provides new insight on the ecology and diversity of Mediterranean deep-sea environments in the 2000 m bathymetric zone, highlighting the enduring knowledge gap surrounding orographically complex deep-sea escarpments in the basin. Highlights: Four benthic assemblages associated to different substrates were identified. On hard substrates sponges and polychaeta were the most abundant and diverse groups. Highest megabenthic organism densities were found on serpulid thanatocoenosis. Lebensspuren likely derived from epibenthic, infaunal and bathypelagic organisms. Litter items had both a marine and land-based origins.